THE DEVELOPMENT OF CURRICULUM BASED ON STRATEGIC THINKING CONCEPT TO ENHANCE FINANCIAL LITERACY FOR UNDERGRADUATE STUDENTS - Wongsrikaew, Kamolsak; Suthasinobon, Kittichai; Langka, Wilailak (Journal of Buddhist Anthropology, 2022)
The objectives of this research article were to develop a curriculum based on the concept of strategic thinking in order to promote financial literacy among undergraduate students. The development of a curriculum consisted of four stages: 1) synthesis of theoretical concepts related to curriculum development as well as interviews with six financial experts; 2) curriculum drafting; 3) assessing the consistency of curriculum components by five experts in instructional curriculum and assessment; and 4) curriculum trial with 18 students in the Faculty of Management Science, Dhonburi Rajabhat University, in order to examine the level of difficulty, discrimination, and reliability of the financial literacy scale and the student’s satisfaction with the curriculum. According to the research results, the developed curriculum comprised seven components: 1) the principles of the curriculum; 2) the objectives of the curriculum; 3) the structure of the curriculum; 4) eight units of learning, namely personal financial management, debt management, financial goal setting, financial planning for retirement, financial markets and instruments, stock investment and how to use stock investment applications, investing in mutual funds and other financial instruments, and investment processes, that are in line with the concept of strategic thinking, which is composed of four steps. 5) the guidelines for organizing learning activities; 6) the learning materials; and 7) the measurement and evaluation. The assessment of the suitability and consistency of the curriculum components revealed that all items were suitable and consistent, with an IOC value of 1.00 for 36 items and 0.80 for 1 item. The difficulty, discrimination, and reliability of the financial literacy scale and the student’s satisfaction with the curriculum were at an acceptable level.